Clinical Associations of Biallelic and Monoallelic TNFRSF13B Variants in Italian Primary Antibody Deficiency Syndromes. (30th March 2016) - Pulvirenti, Federica; Zuntini, Roberta; Milito, Cinzia; Specchia, Fernando; Spadaro, Giuseppe; Danieli, Maria Giovanna; Pession, Andrea; Quinti, Isabella; Ferrari, Simona
Abstract : We assessed the prevalence of TNFRSF13B mutations and the clinical correlates in an Italian cohort of 189 CVID, 67 IgAD patients, and 330 healthy controls to substantiate the role of TACI genetic testing in diagnostic workup. We found that 11% of CVID and 13% of IgAD carried at least one mutated TNFRSF13B allele. Seven per cent of CVID had monoallelic-mutations and 4% had biallelic-mutations. The frequency of C104R monoallelic-mutations was not higher than that found in healthy controls. Biallelic-mutations were exclusively found in CVID. CVID patients carrying monoallelic-mutations had an increased prevalence of lymphadenopathy, granulomata, and autoimmune cytopenias. CVID carrying biallelic-mutations had a low prevalence of autoimmunity in comparison with TACI wild-type CVID. Moreover, biallelic-mutated CVID had higher frequency of switched memory B-cells and higher IgM and IgA antibodies to polysaccharide antigens than TACI wild-type and monoallelic-mutated CVID. TACI-mutated IgAD patients had only monoallelic-mutations and did not display clinical difference from IgAD wild-type patients. In conclusion, TNFRSF13B genetic screening of antibody deficiencies may allow the identification of mutational patterns. However, as with counseling for risk assessment, geneticists should be aware that the interpretation of genetic testing for TACI mutations is difficult and the potential impact on clinical management is still limited.